Bank Profitability and Its Macroeconomic Determinants: Evidence from Indonesian Listed Banks - Salikode, Joshua Marsiko; Siswati, Susi (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2026)
This study aims to examine the effects of the BI Rate, Non-Performing Loans (NPL), and inflation on the profitability of banks listed on the Indonesia Stock Exchange (IDX) during the period 2019–2022. A quantitative research approach was employed to analyze the relationships among the variables. The population of this study consists of 20 banks listed on the IDX within the observation period. Using purposive sampling, 12 banks were selected as the research sample. Secondary data were obtained from published financial statements and macroeconomic indicators, and the data were analyzed using multiple regression analysis. The results of the partial t-test indicate that the BI Rate does not have a significant effect on bank profitability, while Non-Performing Loans (NPL) have a negative and significant effect on profitability. Inflation was also found to have no significant effect on bank profitability. However, the simultaneous F-test results show that the BI Rate, NPL, and inflation jointly have a positive and significant effect on bank profitability. These findings suggest that although individual macroeconomic variables may not significantly influence profitability, credit risk, as reflected by NPL, plays a crucial role in determining bank performance. The study contributes to the existing literature by providing empirical evidence on the impact of macroeconomic factors and credit risk on banking profitability in emerging markets, particularly Indonesia. The results are expected to provide useful insights for bank management, investors, and policymakers in formulating strategies to enhance banking performance and financial stability.